2017
DOI: 10.1002/jcp.25998
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Warburg effect in non‐tumor diseases processes

Abstract: Warburg effect, as an energy shift from mitochondrial oxidative phosphorylation to aerobic glycolysis, is extensively found in various cancers. Interestingly, increasing researchers show that Warburg effect plays a crucial role in non-tumor diseases. For instance, inhibition of Warburg effect can alleviate pulmonary vascular remodeling in the process of pulmonary hypertension (PH). Interference of Warburg effect improves mitochondrial function and cardiac function in the process of cardiac hypertrophy and hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 80 publications
5
97
0
1
Order By: Relevance
“…6F-H). Accumulating evidence indicated that aerobic glycolysis, also named as the Warburg effect, participates in tumor and nontumor diseases (12). Collectively, our data demonstrated that exosomes from activated HSCs induced Warburg effect of recipient KCs and LSECs.…”
Section: Exosomes Derived From Activated Hscs Induced Warburg Effect supporting
confidence: 56%
See 1 more Smart Citation
“…6F-H). Accumulating evidence indicated that aerobic glycolysis, also named as the Warburg effect, participates in tumor and nontumor diseases (12). Collectively, our data demonstrated that exosomes from activated HSCs induced Warburg effect of recipient KCs and LSECs.…”
Section: Exosomes Derived From Activated Hscs Induced Warburg Effect supporting
confidence: 56%
“…It has been reported that aerobic glycolysis, similar to the Warburg effect described in cancer cells, is essential in reprogramming quiescent HSCs into activated HSCs (11). The Warburg effect, as a mechanism of energetic shift, is regarded as the replacement of mitochondrial oxidative phosphorylation with aerobic glycolysis of cancer cells, even in a normoxic environment (12). In the Warburg effect, glucose transporter 1 (GLUT1) acts as a rate-limiting transporter for glucose uptake and promotes diffusion and penetration of glucose and related hexoses into cells, affecting the uptake and utilization of glucose (13).…”
mentioning
confidence: 98%
“…The ability of pathogenic mycobacteria to subvert the host antimicrobial response may lie in its ability to interfere with the metabolic switch to aerobic glycolysis allowing mycobacterial persistence and pathogenicity [167,168]. This shift to aerobic glycolysis and its associated macrophage activation is seen in BCG's effect in T1D [169], MS [170], AD [171] and bladder cancer [172] as well as response to mycobacterial infection [173]. The "Old Friends" theory suggests that microbial exposure at a young age assists the developmental regulation of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In the past ten years, there have been several clinical trials that re-introduce non-pathogenic BCG to stimulate immune remodeling against diverse infectious, autoimmune and allergic diseases [75,76,82,134]. Understanding that aerobic glycolysis, as stimulated by BCG, decreases amyloid-mediated neuronal death perhaps AD will soon be added to this list [154,169].…”
Section: Discussionmentioning
confidence: 99%
“…The latter occurs in glycolysis, the central metabolic pathway in many organisms, including human. A key question is how pathway flux is regulated under dynamic conditions, which happens in nature, biotechnical processes [3][4][5][6] , but also in humans [7][8][9] . Given the task of glycolysis to produce ATP, it is not a surprise that the glycolytic flux is (also) regulated by ATP itself 10,11 .…”
Section: Introductionmentioning
confidence: 99%